Spinal Neoplasm in Dogs - Valentim, Larissa Garbelini; Marcasso, Rogério Anderson; Bracarense, Ana Paula Frederico Loureiro; Arias, Mônica Vicky Bahr (Acta Scientiae Veterinariae, 2016)
Background: Various diseases can cause spinal cord disorders in dogs including neoplasia of the nervous system, which are more common in mature and older animals. Some breeds, as brachycephalics, are more predisposed for certain types of tumors. Spinal neoplasia can be categorized as primary or secondary tumors, and still can be grouped in extradural, intradural/extramedullary or intramedullary. The aim of this study was to investigate the signalment, neurological syndrome, type and source of the mass, presence of metastases, and clinical outcomes in 28 dogs diagnosed with spinal tumors. Materials, Methods & Results: This study included 28 dogs, and in 20 cases, spinal neoplasia was confirmed by necropsy, biopsy, histopathology, and immunohistochemistry. In the other eight animals, the presumptive diagnosis was based on clinical and neurological signs and by observing changes in plain radiographs of the spine, chest radiographs, and myelography. The location of the lesion was established as cervical, cervicothoracic, thoracolumbar, or lumbosacral, and the lesion was determined to be multifocal when clinical signs appeared in more than one location. Spinal cord injury was additionally classified as unilateral, bilateral, symmetrical, or asymmetrical. The following complementary examinations were performed based on the clinical suspicion, indications, and availability of the owner: complete blood count, serum biochemical profile, urinalysis, spinal radiography, cerebrospinal fluid analysis (CSF), myelography, abdominal ultrasound, thoracic X-ray to determine metastases, and Computed Tomography. CSF was collected and analyzed in seven animals, and pleocytosis with a predominance of lymphocytes was found in two cases. Decompression and exploratory surgeries were performed in six dogs to confirm the suspected diagnosis and collect tissues for histopathology. The final diagnosis was made by histopathological examination of the tissue obtained by excisional biopsy or necropsy after the death of the animal or euthanasia. In eight cases, the neoplasia type could not be confirmed as the owner did not provide consent to perform exploratory surgery or necropsy. The dogs most affected were poodles (17.85%) and boxers (17.85%), between the ages of 5 and 10 years, and 67.85% of the cases were female dogs. The thoracolumbar region was the most affected (50%). Metastatic spinal tumors predominated; especially those originating in the mammary gland (38.46%) and on the skin (34.61%), and among the primary neoplasms, meningiomas predominated. The clinical course in relation to the onset of symptoms of neurological dysfunction, until death or euthanasia, ranged from 1-170 days, with an average 42 days of survival. Discussion: The results differ from previous studies, in which the number of male and female dogs with neoplasms in the CNS was the same, as in the present study female dogs were more affected. Unlike other studies, metastatic spinal tumors predominated. After the diagnosis, the survival was short and this may be due to the fact that most dogs in this study already had more than one system affected, and consequently showed significant changes related to systemic metastases during the onset of the neurological symptoms. The surgical treatment presented variable results, and the results observed after surgical resection of neoplasms vary due to the location in relation to the spinal cord, neoplasm type, severity of the clinical signs, and possibility of removal along with margin without causing spinal instability. In dogs with spinal disorders, the veterinary practitioner should suspect cancer, especially if there is a history of excision of neoplasms in other systems.